Effect Perceived of Support and Justice on Deviant Behavior Mediated Emotional Labor in Bhayangkara Hospital - Putri Sari Sumarty Meliala; Rina Anindita; Rokiah Kusumapradja (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Background: Deviant work behavior in the health service sector can reduce the performance of officers and hospital performance. The problem at Bhayangkara Hospital Class IV Mamuju is that there are symptoms of deviant work behavior based on the results of a preliminary survey. Research purposes: The purpose of this research is to provide solutions to efforts to reduce deviant behavior in the workplace by identifying factors such as perceived organizational support, perceived organizational justice, and emotional labor. Research methods: The study used a quantitative causality design that analyzed the causal influence along with descriptive analysis using the three-box method. Respondents consisted of 134 hospital staff. The sampling method used saturated samples or census methods. The data analysis method used partial least square equation modeling. Research result: The results of the study indicate that perceived organizational support has a negative effect on deviant workplace behavior. Perceived organizational justice does not affect deviant workplace behavior. Emotional labor has a positive effect on deviant workplace behavior. Perceived organizational support does not affect emotional labor. Perceived organizational justice has a negative effect on emotional labor. Emotional labor has the greatest effect on changes in deviant workplace behavior compared to perceived organizational support and perceived organizational justice. Conclusion: Providing fair compensation according to the performance of each officer, openness from superiors to their subordinates in explaining work procedures, and managing emotions originating from within the officer will reduce deviant behavior in the workplace.